Perceived duties and responsibilities based on their actual roles as an assistant coach - Altomea, Remelyn P. 1999-
A sport is an activity that requires physical effort and expertise in which one person or team competes against another. A coaching staff, usually composed of a head coach and assistant coaches, is necessary for success. The most prominent leader of the coaching staff is the head coach, while the assistant coach assists and supports the head coach in developing the team's overall program. Assistant coaches must be aware of their duties and responsibilities both on and off the court in order to support the head coach. However, there is a lack of actual evidence on assistant coaches in the Philippines. The purpose of this study is to identify the duties and responsibilities of assistant coaches through the perspective of student-athletes and assistant coaches themselves. Four (4) assistant coaches and (10) student-athletes from a state university were interviewed. The findings revealed that assistant coaches have a variety of duties and responsibilities, both actual and perceived, such as executing and applying drills during training, planning, providing support, being a father figure to athletes, and the relationships they develop with head coaches and athletes. The results of the research are intended to help head coaches, varsity directors, aspiring assistant coaches, and student-athletes in understanding the duties and responsibilities of assistant coaches in different sports.